Gender perspective on teacher-pupil classroom interaction: Feedback and evaluation - Margareta Basaragin; Svenka Savić (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2019)
Various studies confirm the existence of gender bias in classroom interaction and unequal treatment of boys and girls. The aim of this paper is to determinate the differences in the type of teacher’s feedback after female and male pupils’ speech contribution and to explore whether the diverse teacher’s reaction types contribute to the development of different linguistic, gender and cultural identities of pupils in Serbian and Hungarian classes. The corpus was collected during the final year of a bilingual primary school in Subotica (Vojvodina) in 2015 and consists of the fine transcript of two audio and video recordings of mother tongue lessons in Serbian and Hungarian classes. The obtained results confirm the differences in feedback distribution and type in both classes regarding to pupils’ gender. The teachers’ feedback supports higher status of male pupils in the group (class) and in relation to the teachers.v